Association mapping of genetic risk factors for chronic wasting disease in wild deer. (30th August 2012) - Matsumoto, Tomomi; Samuel, Michael D.; Bollinger, Trent; Pybus, Margo; Coltman, David W.
Abstract Chronic wasting disease (CWD) is a fatal transmissible spongiform encephalopathy affecting North American cervids. We assessed the feasibility of association mapping CWD genetic risk factors in wild white‐tailed deer (Odocoileus virginianus) and mule deer (Odocoileus hemionus) using a panel of bovine microsatellite markers from three homologous deer linkage groups predicted to contain candidate genes. These markers had a low cross‐species amplification rate (27.9%) and showed weak linkage disequilibrium (<1 cM). Markers near the prion protein and the neurofibromin 1 (NF1) genes were suggestively associated with CWD status in white‐tailed deer (P = 0.006) and mule deer (P = 0.02), respectively. This is the first time an association between the NF1 region and CWD has been reported.